Hydrogen ion and calcium releasing of MTA Fillapex® and MTA-based formulations - Kuga, Milton Carlos [UNESP]; Campos, Edson Alves [UNESP]; Viscardi, Paloma Hernandez [UNESP]; Carrilho, Paula Zapparoli [UNESP]; Xaviér, Fernanda Castilho [UNESP]; Silvestre, Nayara Pereira [UNESP] (My University, 2011)
MTA is composed of various metal oxides, calcium oxide and bismuth. It has good biological properties and is indicated in cases of endodontic complications. Several commercial formulations are available and further studies are necessary to evaluate these materials. Objective: To evaluate pH and calcium releasing of MTA Fillapex® compared with gray and white MTA. Material and methods: Gray and white MTA (Angelus) and MTA Fillapex® (Angelus) were manipulated and placed into polyethylene tubes and immersed in distilled water. The pH of these solutions was measured at 24 hours, 7 days and 14 days. Simultaneously, at these same aforementioned periods, these materials' calcium releasing was quantified, through atomic absorption spectrophotometry. The results were submitted to ANOVA, with level of significance at 5%. Results: Concerning to pH, the materials present similar behaviors among each other at 24 hours (p > 0.05). At 7 and 14 days, MTA Fillapex® provided significantly lower pH values than the other materials (p < 0.05). Regarding to calcium releasing, at 24 hours and 7 days, MTA Fillapex® provided lower releasing than the other materials (p < 0.05). After 14 days, differences were found between MTA Fillapex® and gray MTA (p < 0.05). Conclusion: All materials showed alkaline pH and calcium releasing, with significantly lower values for MTA Fillapex® sealer.
Keywords: MTA; PH; Calcium; Sealer